Exploring items for measuring self-initiated professional development construct in the context of continuous professional development system usage - Mohd, Noradlina; Azmi Murad, Masrah Azrifah; Omar, Muhd Khaizer (Human Resource Management Academic Research Society, 2023)
Abstract not available.Self-initiated professional development (SI-PD) refers to the proactive engagement of teachers in activities aimed at enhancing their own intellectual capabilities, accumulating practical knowledge and cultivating positive dispositions. This involves the deliberate design, implementation, and evaluation of the learning process, utilising educational resources as a means of support or facilitation. SI-PD is evaluated to determine its effect on the usage of the Continuous Professional Development (CPD) system by Malaysian teachers. There are twenty-six items on the SI-PD, which were adapted from prior studies that employed self-directed learning. The items in this self-directed learning construct have been modified to reflect the context of the CPD system usage. The questionnaire items were then reviewed and verified by the experts from the aspects of content validity, face validity and criterion validity. A pilot study was conducted on 100 teachers who were randomly selected from the central region of Malaysia, which includes three states: Selangor, the Federal Territory of Kuala Lumpur, and the Federal Territory of Putrajaya. Findings of Exploratory Factor Analysis (EFA) yielded five components (motivation, self-monitoring, self-efficacy, self-management, and self-regulation), and internal reliability was achieved for all five components.